Prolonged uterine artery nitric oxide synthase inhibition modestly alters basal uteroplacental vasodilation in the last third of ovine pregnancy - Rosenfeld, Charles R. (American Physiological Society, 2014)
Mechanisms regulating uteroplacental blood flow (UPBF) in pregnancy remain unclear, but they likely involve several integrated signaling systems. Endothelium-derived nitric oxide (NO) is considered an important contributor, but the extent of its involvement is unclear. Bolus intra-arterial infusions of nitro-l-arginine methyl ester (l-NAME) modestly decrease ovine basal UPBF; however, the doses and duration of infusion may have been insufficient. We, therefore, examined prolonged uterine artery (UA) NO synthase inhibition with l-NAME throughout the last third of ovine pregnancy by performing either continuous 30-min UA infusion dose responses (n = 4) or 72-h UA infusions (0.01 mg/ml) at 104–108, 118–125, and 131–137 days of gestation (n = 7) while monitoring mean arterial pressure (MAP), heart rate (HR), and UPBF. Uteroplacental vascular resistance (UPVR) was calculated, and uterine cGMP synthesis was measured. Thirty-minute UA l-NAME infusions did not dose dependently decrease UPBF, increase UPVR, or decrease uterine cGMP synthesis (P > 0.1); however, MAP rose and HR fell modestly. Prolonged continuous 72-h UA l-NAME infusions decreased UPBF ∼32%, increased UPVR ∼68% (P ≤ 0.001), and decreased uterine cGMP synthesis 70% at 54–72 h (P ≤ 0.004); the noninfused uterine horn was unaffected. These findings were associated with ∼10% increases in MAP and decreases in HR that were greater at 104–108 than 118–125 and 131–137 days of gestation (P = 0.006). Although uterine and UA NO and cGMP synthesis increase severalfold during ovine pregnancy, they contribute modestly to the maintenance and rise in UPBF in the last third of gestation. Thus, local UA NO may primarily modulate vasoconstrictor responses. Notably, the systemic vasculature appears more sensitive than the uterine vasculature to NO synthase inhibition.